Whey protein-based bigels for co-encapsulation of curcumin and gallic acid: Characterization, stability and release kinetics - Behnaz Hashemi; Mehdi Varidi; Narjes Malekjani; Seid Mahdi Jafari (Future Foods)
Bigels are a class of soft matter systems with great promise for the food industry as food analogs or as enhanced ingredient substitutes. This work aimed to improve the curcumin (CUR) and gallic-acid (GA) stability, antioxidant capabilities, and controlled release by co-encapsulating them within bigels. This delivery system included a bigel made by whey protein isolate (WPI) aggregates-based oleogel and WPI-based hydrogel in equivalent amounts (50:50). The following techniques were used to evaluate how different bigels affected the chemical stability of CUR and GA: X-ray diffraction (XRD), thermogravimetric analysis (TGA), 1H-nuclear magnetic resonance (1H-NMR), and Fourier infrared (FTIR) spectroscopy. As a result of the protein's ligand-binding abilities, some components may co-adsorb to oil droplet surfaces. Next, it was determined how well the bigels performed as a carrier and looked at their physicochemical stability, digestion, and performance. Examining the release rate of CUR and GA during digestion showed that bigel had a slower release rate (6–15%) than oleogel (16%) and hydrogel (34%), and CUR had a lower release (50%) due to its higher molecular weight and greater entanglement than GA (70%). The stability of bigel (against heat and light) was also higher than oleogel and hydrogel due to having a higher solid component that requires more stress to be applied to the system. CUR and GA had more antioxidant activity in bigel (96.24%) than oleogel (77.71%) and hydrogel (77.34%); which can be attributed to the formation of ultra-fine colloidal dispersions by bigel, allowing more CUR and GA to interact with free radicals by creating more contact surface. The multi-functional bigels showed great potential for delivering antioxidants to the intestine while enhancing their stability. Hydrophobic interactions and hydrogen bonding between WPI and CUR-GA were validated by FTIR analysis, that kept bigels stable. Overall, our findings demonstrated that WPI-based bigels with intriguing UV light, color, and thermal stability could be developed. This would increase the use of bigels in innovative food products with high nutritional value.